Cytotoxoic effect of Laurus nobilis extract on different cancer cell lines (Journal of the College of Basic Education, 2022)
Bay leaf belongs to the family Lauraceae, and it is one of the most popular culinary spices in all Wstern counteries. Bay leaf has been used as herbal medicine and it has pharmacological activity, antibacterial, antifungal, antidiabetes, antiinflammatory effects and cytotoxic activities. In this stud, the effect of laurus nobilis hexan extract on three different cell lines was investigate in an attempt to identfy its potential activity